A Fully Non‐fused Ring Acceptor with Planar Backbone and Near‐IR Absorption for High Performance Polymer Solar Cells - Chen, Ya‐Nan; Li, Miao; Wang, Yunzhi; Wang, Jing; Zhang, Ming; Zhou, Yuanyuan; Yang, Jianming; Liu, Yahui; Liu, Feng; Tang, Zheng; Bao, Qinye; Bo, Zhishan (Angewandte Chemie International Edition, 2020)
Fused‐ring electron acceptors have made significant progress in recent years, while the development of fully non‐fused ring acceptors has been unsatisfactory. Here, two fully non‐fused ring acceptors, o‐4TBC‐2F and m‐4TBC‐2F, were designed and synthesized. By regulating the location of the hexyloxy chains, o‐4TBC‐2F formed planar backbones, while m‐4TBC‐2F displayed a twisted backbone. Additionally, the o‐4TBC‐2F film showed a markedly red‐shifted absorption after thermal annealing, which indicated the formation of J‐aggregates. For fabrication of organic solar cells (OSCs), PBDB‐T was used as a donor and blended with the two acceptors. The o‐4TBC‐2F‐based blend films displayed higher charge mobilities, lower energy loss and a higher power conversion efficiency (PCE). The optimized devices based on o‐4TBC‐2F gave a PCE of 10.26 %, which was much higher than those based on m‐4TBC‐2F at 2.63 %, and it is one of the highest reported PCE values for fully non‐fused ring electron acceptors. Two fully non‐fused acceptors are precisely designed and easily prepared. The side chain encapsulation can induce a planar molecular backbone conformation, endowing the acceptor with broad light absorption. Thermal annealing promotes molecular rearrangement to form J‐aggregates with even broader absorption and higher absorption coefficient. A PCE over 10 % is one of the highest PCE for fully non‐fused ring acceptors.